PERAN PENDEKATAN STUDENT CENTER LEARNING DALAM PROSES PEMBELAJARAN DI PRODI D-III KEPERAWATAN POLTEKKES KEMENKES BENGKULU - Efendi, Pauzan (JURNAL MEDIA KESEHATAN, 2016)
Student Centre Learning (SCL) is a learning strategy that puts students aslearners active and independent, with a psychological condition as an adult learner, areentirely responsible for learning, as well as being able to learn beyond the classroom(Harsono, 2008). The application of learning methods SCL on CBC be separate stimulusfor students, because of changes in various factors, both in the learning objectives,learning targets, and the role of students in the learning process. The purpose of researchis to know the description SCL's implementation approach at D III Nursing ProgramsBengkulu Poltekkes MoH in accordance with operational guidelines, find a picture of theimpact of the implementation of the SCL approach to students and lecturers as well asknow the description of perception of students and lecturers of the implementation of theSCL approach. The results of observation curriculum and kaldek and good interviewswith faculty and learners obtained the subject states have implemented learning systemwith subjects integrated with the system block and method of approach SCL throughCBL, CL, CI, SGD and others in order to subject more akatif and independent in thelearning process. The subjective perception of both lecturers as facilitators and subject aslearners have the same perception that the SCL method is able to activate andindependence . Methods of SCL is a learning strategy that puts students as active andindependent learners, faculty and partners act as a facilitator of learning. On learningoutcomes when viewed with the value, performance approach methods SCL in the studyprogram diploma three Nursing Bengkulu has not shown any significant improvement,however, evaluation of learning outcomes to be especially helpful personal developmentboth lecturers as facilitators and learners in achieving the learning objectives appropriatecompetencies expected. SCL expected learning method is not only a major impact onstudents but also requires a great contribution of lecturers and educational facilities. Ittakes a number of lecturers and adequate facilities for learning effectiveness can befulfilled with the SCL method. Besides the ability of the entire faculty are similar infacilitating the learning process is very important that all students obtain a similar learningexperience as well.